(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The importance of female entrepreneurs is growing in India, following the trends of monetary liberalisation and globalisation. The institutional and governmental framework for encouraging entrepreneurial skills, offering vocation education, and educating children has opened new doors for women’s economic empowerment. This gives women greater chances to achieve financial independence. However, only around one third of the employment in financial institutions is made up of women. The entrepreneurial aspirations of women are inextricably linked to the improvement of society and economic prosperity. Women make up a relatively small percentage of those involved in entrepreneurship-related activities. The proportion of female business owners has increased significantly in almost all economies. Although the Haryana government has implemented a number of legislation to encourage the establishment of women-owned businesses in both rural and urban regions, there have been significant difficulties in putting these policies into practise. Women’s latent entrepreneurial potential has come to light as a result of growing awareness of both the social and economic roles that they play in society. Women are starting businesses for a number of reasons, but their increasing business knowledge, skills, and compliance with regulations are among the most crucial.